Effect of Trichormus variabilis biomass concentration and application method on cucumber growth under Cucumber Green Mottle Mosaic Virus (CGMMV) infection - ZEAYD TAREQ ALANGOOD; MAADH A. AL-FAHAD (Smujo International, 2026)
Abstract. Alangood ZT, Al-Fahad MA. 2026. Effect of Trichormus variabilis biomass concentration and application method on cucumber growth under Cucumber Green Mottle Mosaic Virus (CGMMV) infection. Asian J Agric 10 (1): g100154. https://doi.org/10.13057/asianjagric/g100154. This study evaluated the effect of cyanobacterium Trichormus variabilis biomass on cucumber (Cucumis sativus) performance under Cucumber Green Mottle Mosaic Virus (CGMMV) infection in open-field conditions. Viral infection was confirmed using CGMMV-specific ImmunoStrip assays prior to treatment application. The experiment was arranged in a factorial design including three concentrations of T. variabilis dried biomass suspension (50%, 75%, and 100%) and three application methods (seed soaking, foliar spraying, and soil drenching), in addition to healthy and infected controls. Biomass concentrations significantly influenced disease severity, disease incidence, chlorophyll content (SPAD), fruit weight, and fruit firmness. The 75% concentration consistently reduced disease severity and incidence and improved physiological and yield-related traits compared with the 50% concentration. For several parameters, no significant differences were detected between the 75% and 100% concentrations, indicating a plateau response at higher biomass levels. Application method had limited influence on most measured traits. Differences in hydrogen peroxide (H₂O₂) accumulation were observed using a potassium iodide (KI)-based qualitative assay, indicating relative variation in oxidative status among treatments. The study was conducted during a single growing season, at one field location, and on a single cucumber cultivar, further multi-environment validation and standardized biomass characterization are required before making broader recommendations can be made. Overall, T. variabilis biomass at an intermediate concentration mitigated CGMMV-associated disease symptoms and improved cucumber productivity under the tested conditions.